2002
DOI: 10.1093/cercor/12.4.386
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Neuronal Size and Glial Cell Density in Area 9 of the Dorsolateral Prefrontal Cortex in Subjects with Major Depressive Disorder

Abstract: Reductions in glial cell density and neuronal size have been described recently in major depressive disorder (MDD). Considering the important trophic influence of glia on neurons, we hypothesized that this glial cell deficit is more prominent close to neurons. In this investigation we have characterized neuronal and glia cytoarchitecture in prefrontal area 9 using spatial point pattern techniques and two-dimensional measures of cell size and density. In post-mortem brain tissue of subjects with MDD, schizophre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
362
3
8

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 548 publications
(399 citation statements)
references
References 56 publications
26
362
3
8
Order By: Relevance
“…The present observations of reductions in specific subpopulations of neurons immunoreactive for calcium binding proteins in MDD are in good agreement with earlier reports of reductions in the neuronal density and/or size of the Nissl-stained general population of neurons in the dlPFC and ORB regions in MDD (Cotter et al, 2002b(Cotter et al, , 2005Rajkowska et al, 1999). In those studies, neuronal pathology was observed in the same cortical layers (II-VI) as in the present study.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The present observations of reductions in specific subpopulations of neurons immunoreactive for calcium binding proteins in MDD are in good agreement with earlier reports of reductions in the neuronal density and/or size of the Nissl-stained general population of neurons in the dlPFC and ORB regions in MDD (Cotter et al, 2002b(Cotter et al, , 2005Rajkowska et al, 1999). In those studies, neuronal pathology was observed in the same cortical layers (II-VI) as in the present study.…”
Section: Discussionsupporting
confidence: 94%
“…Morphometric studies in post-mortem tissue have demonstrated reductions in the average density and size of Nissl-stained neurons in the dorsolateral prefrontal cortex (dlPFC) and orbitofrontal cortex (ORB) in major depressive disorder (MDD) (Cotter et al, 2002b(Cotter et al, , 2005Rajkowska et al, 1999). The neuronal pathology was most prominent in layer II of ORB and in layers II, III, V, and VI of dlPFC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As stress is associated with the risk of developing depression (Kessler, 1997;Kendler et al, 1999), the morphological findings of preclinical studies, where animals are exposed to chronic stressful experiences, are commonly related to the structural changes reported in the brains of depressed patients. In vivo imaging studies reveal selective volume reduction in the PFC (Drevets, 2000), and post mortem histological data show reductions in neuronal size and glial cell numbers in specific subregions of the frontal cortex in depressed patients (Ö ngür et al, 1998;Rajkowska et al, 1999;Cotter et al, 2001aCotter et al, , 2002Uranova et al, 2004). It is tempting to speculate that our finding on the pronounced changes in gliogenesis after chronic stress exposure may relate to the abnormalities of glial cell numbers reported in the frontolimbic areas of depressed patients.…”
Section: Stress-induced Structural Changes and Their Potential Implicmentioning
confidence: 76%
“…Post-mortem studies of glial cell pathology in depression have reinforced this concept, although findings remain conflicted in many cases. [43][44][45][46] The observation of a significant misexpression of molecules central to both GABAergic and glutamatergic neurotransmission in the cortical areas of individuals with major depression has been previously documented by several groups. 21,23,47 These studies follow on a body of clinical evidence showing that antidepressant medications may reduce glutamatergic activity while raising cortical GABA levels, which are seen to be reduced in major depression 48,49 and possibly also schizophrenia.…”
Section: Discussionmentioning
confidence: 95%